Classroom interaction in EMI high schools: Do teachers who are native speakers of English make a difference?. (June 2021) - An, Jiangshan; Macaro, Ernesto; Childs, Ann
Abstract: English Medium Instruction (EMI) in secondary education has increasingly become a focus of research. One dimension of this research has been on whole-class interaction patterns of teachers and students, interaction having been established as important for learning in both second language (L2) contexts and in content subjects such as science. Previous EMI studies have reported teacher dominance of the interaction and low levels of student participation. A possible explanation has been that research hitherto has investigated mostly local EMI teachers who have been reported to lack the linguistic proficiency to engage in 'unscripted' interaction. To explore this we investigated the interaction patterns of 15 secondary science teachers in EMI high school programs in China, for whom English was their first and most proficient language in order to eliminate the teacher language proficiency issue. Our findings show that interaction was similarly teacher dominated and students' responses were of low linguistic complexity. Suggestions for further research to identify the reason for low student participation are given, together with some implications for EMI teacher professional development.